Optimum design of large-scale truss towers using cascade optimization - Kaveh, A.; Ilchi Ghazaan, M. (Acta mechanica, 2016)
High number of design variables, large size of the search space, and control of a great number of design constraints are major preventive factors in performing optimum design of real-world structures in a reasonable time. The present study intends to examine the computational performance of cascading in design optimization of truss towers with large numbers of design variables. The cascade optimization procedure utilized in this paper reduces the objective function value over a number of optimization stages by initially operating on a small number of design variables, which is gradually increased stage after stage. In fact, the early stages of optimization in the cascade procedure make use of the coarsest configurations with small numbers of design variables and the later stages exploit finer configurations with larger numbers of design variables. The optimization algorithm utilized in each stage of a cascade process is enhanced colliding bodies optimization. High solution accuracy and convergence speed of the proposed method are shown through three test examples.